PERBAIKAN MESIN PEMISAH TATAL PADA PROSES SPRUECUT DEBURING DI PT. PAKOAKUINA MOTORCYCLE - , RIEZA MAHENDRA, Ir. Tarmono, MT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Spruecut deburing is a machining process on manufacture of rim for removing the sprue and riser on the rest of rim as the casting results. Chips separator machine is a tool for separating which has large dimension sprue and riser with flaky produced by machining processes. The fact proves that the large dimension chips and the flakes still mixed. While PT. Pakoakuina Motorcycle are fused back in raw material, therefore the sprue and risers must be separated with flakes of chips Base on the issue above, the experiment is carried on PT Pakoakuina Motorcycle to optimized the process that repair is required. The method applied is the data collection and information about the separation of chips. The chips separator machine is repaired used vibrator. The efficient and effective separator machine modified is achieved The result shows that separated chips machine which has modified is the one solution to optimize the sprue and riser with the chips flakes separation in spruecut deburing processes. The flakes of chips that attached to the sprue and riser is decreased, for 85 percent which 2 kg to 0,3 kg. The cassinogenic from smoke, melting process, ash, dust and other pollutant can be reduced by this method. The efficiency benefit annual is 12852 kg